2011
DOI: 10.1111/j.1570-7458.2010.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

The parasitoid fly Exorista japonica uses visual and olfactory cues to locate herbivore-infested plants

Abstract: Some parasitoid flies exploit odors derived from plants as olfactory cues for locating the food plants of host insects, but the role of visual cues associated with plants remains largely unknown. The generalist tachinid Exorista japonica Townsend (Diptera: Tachinidae) is attracted to odors derived from maize plants [Zea mays L. (Poaceae)] infested by the larvae of Mythimna separata (Walker) (Lepidoptera: Noctuidae). In this study, we examined the effects of visual parameters on the olfactory attraction of fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…(Coleoptera: Nitidulidae). Finally, the tachinid parasitoid Exorista japonica Townsend uses both visual and olfactory cues to locate the host habitat of the noctuid pest Mythimna separata (Walker) (Ichiki et al 2011).…”
Section: Wavelength (Nm)mentioning
confidence: 99%
“…(Coleoptera: Nitidulidae). Finally, the tachinid parasitoid Exorista japonica Townsend uses both visual and olfactory cues to locate the host habitat of the noctuid pest Mythimna separata (Walker) (Ichiki et al 2011).…”
Section: Wavelength (Nm)mentioning
confidence: 99%
“…Our previous study showed that E. japonica females were attracted to odors from corn plants infested with lastinstar larvae of M. separata Ichiki et al 2008Ichiki et al , 2011Hanyu et al 2009) and also attracted to odors from corn plants artificially damaged with a punch (Hanyu et al 2009). The previous study also showed different durations of attraction time for infested and artificially damaged plants.…”
Section: Introductionmentioning
confidence: 97%
“…The types and amounts of volatiles differ between plant species, attacking herbivores, and herbivore developmental stages (Vet and Dicke 1992;Gouinguené et al 2003;Yan and Wang 2006). Many studies report that herbivore-infested plants that emit HIPVs attract a number of hymenopteran parasitoids (e.g., Turlings et al 1990;Takabayashi et al 1995;Fukushima et al 2002;Shiojiri et al 2006;Bruinsma et al 2009) and several dipteran parasitoids (Roth et al 1982;Roland et al 1989;Mondor and Roland 1997;Kainoh et al 1999;Stireman 2002;Ichiki et al 2008Ichiki et al , 2011Hanyu et al 2009). These reports indicate HIPVs play an important role in the host-searching behavior of tachinid flies.…”
Section: Introductionmentioning
confidence: 97%
“…For diurnal insects, we established wind tunnel experiments for Aphidius colemani in our laboratory and used a light intensity of 150 lx, because female A. colemani did not show good orientation toward the odor source (herbivore damaged plant) under lighter conditions and flew upward to the ceiling of the tunnel at 2,000 lx (Fujinuma et al, unpublished). However, the tachinid fly Exorista japonica readily flew to the target plant under full light conditions (>2,000 lx) (Kainoh et al, 1999;Ichiki et al, 2008Ichiki et al, , 2011Hanyu et al, 2009). As a light source, we use Vitalite ® (40W, 6 tubes) to maintain light conditions similar to sunlight, and the light intensity can be changed with a voltage converter from 0 to 6,000 lx.…”
Section: Light Sourcementioning
confidence: 99%
“…A wind tunnel is one olfactometer used as a bioassay method of olfactory stimuli. Wind tunnel tests have been widely used in insect pheromone research (e.g., Baker and Linn, 1984;Kainoh et al, 1984;Hiyori et al, 1986a,b), to study plant volatiles as kairomones (e.g., Kainoh et al, 1980) and to study synomones (e.g., Kainoh et al, 1999;Fukushima et al, 2001Fukushima et al, , 2002Ichiki et al, 2008Ichiki et al, , 2011. Sabelis and van de Baan (1983) used a Y-tube olfactometer and determined that predacious mites responded to the odors of plants infested with spider mites.…”
Section: Introductionmentioning
confidence: 99%